"It's been a helluva year": the experience of vestibular disorders on the significant other's quality of life - Berry, Natanya Lee (My University, 2017)
In health care, there appears to be greater consideration for the biopsychosocial model of disability and viewing disability in terms of functional health. Recently, the effect of impairment on the significant other’s (SO’s) quality of life (QOL) has been explored. In audiology, there appear to be very few published studies in this area, particularly related to vestibular disorders. The purpose of this study was to investigate the experiences of vestibular disorders on the SO’s QOL. A qualitative research design was employed, including 11 interviews and two focus groups. Participants were SO’s of individuals with chronic vestibular disorders, and were recruited from a private audiology practice in Gauteng through purposive sampling strategies. Data were analysed using thematic analysis. Eight primary themes emerged in the data analysis: social implications, financial implications, searching for a diagnosis, emotional effects, changes in family dynamics, support systems, comparison-oriented coping mechanisms, and referrals for psychological services. Findings suggested that SO’s experienced third-party vestibular disability; however, having the appropriate support systems, including family and friends, was pertinent. It was also indicated that the relationship with the audiologist was essential in providing better understanding of the condition and prognosis thereof, resulting in less frustration and improved adaptation to the reported changes. A key finding was the lack of referral for psychological or counselling services. These findings suggest the need to account for third-party vestibular disability in clinical, theoretical, and academic settings, and they call for the inclusion of third-party disability in policy-making.
A dissertation on a study presented to the Discipline of Speech Pathology and Audiology , School of Human and Community Development , Faculty of Humanities , University of the Witwatersrand , In fulfilment of the requirements for the degree M.A. Audiology , March 2017
Keywords: Vestibular apparatus--Diseases; Hearing disorders--Diseases